Prevalence of maxillary canine palatal impaction in 10- 11 years old children in Mashhad - A Sarraf Shirazi; F Ahrari; B Baghaee (Isfahan University of Medical Sciences, 2008)
Introduction: There are different reports about the rate of maxillary canine impaction in different communities and races. The aim of this study was to determine the prevalence of maxillary canine palatal impaction in 10-11 years old children in Mashhad.Methods and Materials: In this descriptive cross sectional study, 1472, 10-11 years old students in Mashhad were selected through random cluster sampling process. Dental age was considered as an important criterion in clinical diagnosis of impaction. Suspected children to impaction in clinical examination were referred to Mashhad Dental School for radiographic examination and preventive treatment. The condition of lateral incisor teeth was inspected in children who were suspected to impaction. The data were analyzed using descriptive statistics and Fischer's exact test.Results: Considering dental age, 5.5% of children were suspected to impaction in clinical examination and referred for radiographic examination. The prevalence of maxillary canine palatal impaction in the population evaluated was 1.1%. Impaction was more prevalent in girls comparing to boys. There was an association between palatal positions of maxillary canines and missing or peg shaped lateral incisors (p value